Find the product using identities( 2x +3) (2x – 3)
Shweta9904:
4x^2 - 9 is the right answer
Answers
Answered by
3
identity = (a + b) (a - b) = a² - b²
a = 2x
b = 3
a² - b²
(2x)² - (3)²
4x² - 9
a = 2x
b = 3
a² - b²
(2x)² - (3)²
4x² - 9
Answered by
0
identity=(a+b) (a-b) = a2-b2
![a = 2x a = 2x](https://tex.z-dn.net/?f=a+%3D+2x+)
![b = 3 b = 3](https://tex.z-dn.net/?f=b+%3D+3)
![{(2x)}^{2} - {(3)}^{2} {(2x)}^{2} - {(3)}^{2}](https://tex.z-dn.net/?f=+%7B%282x%29%7D%5E%7B2%7D+++-+%7B%283%29%7D%5E%7B2%7D+)
![{4x}^{2} - 9 {4x}^{2} - 9](https://tex.z-dn.net/?f=+%7B4x%7D%5E%7B2%7D++-+9)
Similar questions